Host plant richness and environment in tropical forest transformation systems shape arbuscular mycorrhizal fungal richness - Edy, Nur; Barus, Henry Novero; Finkeldey, Reiner; Polle, Andrea (Frontiers in Plant Science, 2022)
Transformation of tropical lowland rain forests into rubber tree and oil palm plantations is the cause of massive loss of vegetation diversity. The consequences for associated mycorrhizal fungi are not fully understood. We hypothesized that generalist arbuscular mycorrhizal fungi are resistant to removal of host species richness and that forest conversion to oil palm and rubber leads to loss of arbuscular mycorrhizal fungal (AMF) species with host preferences. Plant identities and AMF species were determined by molecular barcoding of 112 roots collected in three land-use systems (rain forest, rubber tree and oil palm plantation) in two landscapes on Sumatra (Indonesia), a world hotspot of forest transformation. The collected roots were from 43 forest plant species, in addition to rubber trees and oil palms. We detected 28 AMF species of which about 75% were present in forest trees and 25% shared among the land use systems. Only one AMF species present in plantation roots was not detected in the analyzed forest roots. Host specificity of arbuscular mycorrhizal fungi was not detected. Oil palm and rubber tree roots exhibited a strong reduction in AMF richness compared with roots from rainforests and were differentiated by soil resources. On basis of an individual root, oil palm had a lower AMF species richness than forest or rubber tree roots. Our results demonstrate that tropical AMF communities are shaped by two mechanisms: (i) root habitat diversity as the result of plant diversity and (ii) habitat properties as the result of plant traits or environmental conditions and management. Collectively, deterioration of habitat diversity and properties exacerbates impoverishment of AMF assemblages.